STRATEGI DAKWAH IPPNU SUKOHARJO DALAM MENGUATKAN MODERASI BERAGAMA - Annisa Choirunnisa Annisa Choirunnisa; Abraham Zakky Zulhazmi (An-Nida : Jurnal Komunikasi Islam, 2022)
Da'wah strategy is a method, tactic, tactic used in da'wah activities or activities, whose role is very decisive in the process of achieving da'wah goals. In the process of da'wah, the important thing that must be considered is the da'wah strategy. The purpose of this study was to determine the da'wah strategy used by the IPPNU Autonomous Body in Sukoharjo Regency. This study uses a qualitative method, with a phenomenological approach. Data collection techniques using interviews. The author uses books, documents, articles, journals and information from interviews to complete this research. The findings of this study include: 1) As an organization Nahdlatul Ulama (NU) uses a good strategy in carrying out Islamic da'wah. 2) The da'wah strategy used by IPPNU includes strategies in the fields of arts and culture, in the field of sports, in the field of da'wah, in the field of communication and information and cadre for its congregation. Activities carried out are daily, weekly and even yearly. The recommendation in this study is the existence of continuous research on the propaganda strategy of the IPPNU Autonomous Agency in Sukoharjo Regency and can mingle with other Muslims in carrying out their duties.